Growth in post-industrial cities: an endogenous model - Riccardo Cappellin (European Regional Science Association (ERSA), 2012)
The role of the growth of new activities in an urban economy can be explained by means of three models: a supply, a demand, and a network model. First, the growth of the supply in a new sector may determine a corresponding increase in the demand and the product of the area considered. Second, cities may internally develop new sectors which may respond to the demand of local consumers and to the needs for intermediate inputs of exporting firms. Third, new knowledge promotes the continuous differentiation of the internal needs and demand of users and the reconversion of the specialized human capabilities and internal supply, thus enhancing the creation of new firms and employment. Economic growth is tightly linked with the turnover of productions and of firms, and it is determined by a Schumpeterian process of creation of new productions, new skills and new preferences which replace traditional productions, skills and preferences. According to this model, the role of national and local governments is to promote the growth of internal demand and to create institutions and physical infrastructures in order to facilitate the process of interactive learning, which leads to knowledge creation in urban areas.
Keywords: 330